2020
DOI: 10.3847/2041-8213/ab72a5
|View full text |Cite
|
Sign up to set email alerts
|

13CH3OH Masers Associated With a Transient Phenomenon in a High-mass Young Stellar Object

Abstract: We report the first detection of isotopic methanol ( 13 CH 3 OH) maser emission in interstellar space. The emission was detected toward the high-mass young stellar object G358.93-0.03 during monitoring of a flare in the 6.7 GHz methanol (CH 3 OH) maser emission in this source. We find that the spectral and spatial distribution of the 13 CH 3 OH masers differs from the CH 3 OH masers imaged at the same epoch, contrary to expectations from similarity of their pumping. This conclusively demonstrates that isotopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…A similar 6.7 GHz CH 3 OH maser flare was also detected in NGC6334I-MM1 (Hunter et al 2018;MacLeod et al 2018), along with a 22 GHz water (H 2 O) maser burst (Brogan et al 2018). Another HMYSO G358.93-0.03-MM1 (Sugiyama et al 2019;Burns et al 2020) showed a flare of the 6.7 GHz CH 3 OH masers and other new methanol transitions (Breen et al 2019;Brogan et al 2019;MacLeod et al 2019;Chen et al 2020), a result of the recent extensive observations by the global collaboration network "Maser Monitoring Organization" (M2O; MaserMonitoring.org). The outbursts from these HMYSOs represent a unique opportunity to investigate the accretion and, in turn, ejection processes in these objects and derive useful parameters, such as the mass accretion and ejection rates, infall velocity, and duration of the events.…”
Section: Introductionmentioning
confidence: 78%
“…A similar 6.7 GHz CH 3 OH maser flare was also detected in NGC6334I-MM1 (Hunter et al 2018;MacLeod et al 2018), along with a 22 GHz water (H 2 O) maser burst (Brogan et al 2018). Another HMYSO G358.93-0.03-MM1 (Sugiyama et al 2019;Burns et al 2020) showed a flare of the 6.7 GHz CH 3 OH masers and other new methanol transitions (Breen et al 2019;Brogan et al 2019;MacLeod et al 2019;Chen et al 2020), a result of the recent extensive observations by the global collaboration network "Maser Monitoring Organization" (M2O; MaserMonitoring.org). The outbursts from these HMYSOs represent a unique opportunity to investigate the accretion and, in turn, ejection processes in these objects and derive useful parameters, such as the mass accretion and ejection rates, infall velocity, and duration of the events.…”
Section: Introductionmentioning
confidence: 78%
“…Note that the only centimetre observations found in the literature on the pre-burst epoch are those of Hu et al (2016), who report a null detection at C-band, but based on only 20 seconds of data. The latest VLA B-array observation of Chen et al (2020a) also reported a non-detection of Ku-band continuum emission in the direction of MM1 at 3σ level of 20 µJy.…”
Section: Continuum Emissionmentioning
confidence: 98%
“…All these findings suggest the impact of the outflow/jet to the ambient gas around W42-MME, which is an IRc of the 6.7 GHz MME. Recently, flaring methanol masers have been found to trace episodic accretion events in young protostars (e.g., Bertout 1989;Hirota et al 2018;Hunter et al 2018;MacLeod et al 2018;Chen et al 2020;Liu et al 2020;Zinchenko et al 2020;Stecklum et al 2021). Hence, our findings appear to show the episodic ejection from W42-MME.…”
Section: Signature Of An Episodic Accretion Processmentioning
confidence: 99%